Postprandial glycemia in healthy subjects: Which probiotic dairy food is more adequate? - Grom, L.C.; Rocha, R.S.; Balthazar, C.F.; Guimarães, J.T.; Coutinho, N.M.; Barros, C.P.; Pimentel, T.C.; Venâncio, E.L.; Collopy Junior, I.; Maciel, P.M.C.; Silva, P.H.F.; Granato, D.; et al. (Journal of dairy science, 2020)
The consumption of probiotic-enriched dairy products has been associated with many health benefits, including anti-hyperglycemic activity. The effect on health is dependent on the type of probiotic culture used and the dairy product consumed. This study evaluated the effect of different probiotic-enriched dairy matrices (Minas Frescal cheese, Prato cheese, and whey dairy beverage) containing Lactobacillus casei on in vitro and in vivo anti-hyperglycemic activity. For this purpose, in vitro anti-hyperglycemic activity was determined by the inhibition of α-glucosidase and α-amylase activities, and a human study was performed with healthy individuals (n = 15, consumption of bread as a control; bread + Minas Frescal cheese; bread + Prato cheese; bread + dairy beverage) to assess the effects of different probiotic foods on postprandial glycemia. In vitro data showed that Prato cheese presented the highest lipid (36.9 g/100 g) and protein (26.5 g/100 g) contents as well as the highest α-amylase (60.7%) and α-glucosidase (52.6%) inhibition. The consumption of Prato cheese resulted in a lesser increase in blood glucose level (13 mg/dL) compared with the consumption of bread alone (19 mg/dL), Minas Frescal cheese (20 mg/dL), and whey dairy beverage (30 mg/dL), with glycemic indices similar to that observed for the control. The present results demonstrated a good correlation between in vitro and in vivo data, in which the type of dairy matrix affects the anti-hyperglycemic activity. It is concluded that the consumption of probiotic Prato cheese can contribute to the reduction of postprandial glycemia in healthy individuals.